The Importance of Escape Clauses: Firm Response to Thin Capitalization Rules - Martin Eckhoff Andresen; Lars Thorvaldsen (Center for Economic Studies and ifo Institute (CESifo), 2022)
Escape clauses, where small firms are exempt from particular tax rules, is a crucial feature of a number of corporate tax schemes, but creates incentives to avoid taxation by manipulating the measures that determine inclusion. We evaluate the impact of thin capitalization rules, which commonly feature such escape clauses across the world, by exploiting the introduction of these rules in Norway in 2014. Combining difference-in-differences, regression discontinuity and bunching estimates, we show that what appears to be a strong response in the capital structure among exposed firms primarily reflect within-group reallocation of debt to avoid exposure to the rules. We observe sharp bunching among both new and existing subsidiaries at both thresholds for rule inclusion, and find that internal corporate group debt is offloaded to these bunching subsidiaries in order to avoid additional tax costs. As a result, significant and large effects on firm-level capital structure in response to the thin capitalization rules is driven by reshuffling of capital within corporate groups with little real effects. Re-estimating the difference-in-difference specification at the corporate group level confirms this finding, questioning the extent to which thin capitalization rules affect the real economy due to the presence of escape clauses.
Keywords: H25; H26; G30; 330; thin capitalization rules; capital structure; escape clauses; difference-in-differences; bunching